Invasive Squamous Cell Carcinoma of Anterior Mediastinum of Unknown Primary Site - Bibek Koirala; Min Zhang; Ali Akalin (Annals of Internal Medicine: Clinical Cases)
The most common lesions in the anterior mediastinum are thymomas, lymphomas, teratomas, and thyroid masses. Squamous cell carcinoma of anterior mediastinum is most commonly due to thymic carcinoma. We present an unusual case of a patient presenting with anterior mediastinal mass that was later found to be biopsy-proven invasive squamous cell carcinoma of unknown primary site based on the available imaging studies. We also review the broad differential diagnoses, clinical presentation, and diagnostic work-up of anterior mediastinal mass, especially the one with no clear primary site.